ENDOSCOPIC SCLEROTHERAPY OF ESOPHAGEAL VARICES INCREASES GASTROESOPHAGEAL REFLUX - S. KAYMAKOĞLU; G. BOZTAŞ; Z. MUNGAN; S. ÖZDİL and I. ADALET and Y. ÇAKALOĞLU and F. BEŞIŞIK and O. YEĞİNSÜ and N. EROL and A. ÖKTEN and et al. (Turkish Journal of Gastroenterology, 2020)
-